2011
DOI: 10.1016/j.jneumeth.2011.06.001
|View full text |Cite
|
Sign up to set email alerts
|

Recording the adult zebrafish cerebral field potential during pentylenetetrazole seizures

Abstract: Although the zebrafish is increasingly used as a model organism to study epilepsy, no standard electrophysiological technique for recording electrographic seizures in adult fish exists. The purpose of this paper is to introduce a readily implementable technique for recording pentylenetetrazole seizures in the adult zebrafish. We find that we can consistently record a high quality field potential over the zebrafish cerebrum using an amplification of 5000 V/V and bandpass filtering at corner frequencies of 1.6 a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
55
1
3

Year Published

2012
2012
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(60 citation statements)
references
References 38 publications
1
55
1
3
Order By: Relevance
“…Mature zebrafish, which possess well-developed endocrine, sensory, and motor systems (Bally-Cuif and Vernier 2010), a range of complex behaviours such as social interactions (Saverino and Gerlai 2008), learning and memory (Gomez-Laplaza and Gerlai 2010; Norton and Bally-Cuif 2010;Al-Imari and Gerlai 2008) and a physiology similar to mammals (Bally-Cuif and Vernier 2010), have been recognized as beneficial to investigations of neurological diseases (Alfaro et al 2011;Siebel et al 2011;Wong et al 2010;Keller and Murtha 2004;Mathur and Guo 2010;Ramirez et al 2012;Haud et al 2011;Williams et al 2011). As adult zebrafish continue to be used as an experimental model, new techniques are being developed to better characterize their behaviour , neuronal activity (Pineda et al 2011), neurochemistry (Kabli et al 2009) and neuromorphology (Rao et al 2009;Ullmann et al 2010b;Ullmann et al 2010a; Kabli et al 2006). …”
Section: Introductionmentioning
confidence: 99%
“…Mature zebrafish, which possess well-developed endocrine, sensory, and motor systems (Bally-Cuif and Vernier 2010), a range of complex behaviours such as social interactions (Saverino and Gerlai 2008), learning and memory (Gomez-Laplaza and Gerlai 2010; Norton and Bally-Cuif 2010;Al-Imari and Gerlai 2008) and a physiology similar to mammals (Bally-Cuif and Vernier 2010), have been recognized as beneficial to investigations of neurological diseases (Alfaro et al 2011;Siebel et al 2011;Wong et al 2010;Keller and Murtha 2004;Mathur and Guo 2010;Ramirez et al 2012;Haud et al 2011;Williams et al 2011). As adult zebrafish continue to be used as an experimental model, new techniques are being developed to better characterize their behaviour , neuronal activity (Pineda et al 2011), neurochemistry (Kabli et al 2009) and neuromorphology (Rao et al 2009;Ullmann et al 2010b;Ullmann et al 2010a; Kabli et al 2006). …”
Section: Introductionmentioning
confidence: 99%
“…Numerous studies have showed that adult or zebra-fish larvae exposed to PTZ exhibit increased locomotor activity, seizure-like behavior, and epileptiform electrographic activity [15,19] [ [22][23][24], which have a good correlation between zebra-fish and rodent data [15,17,21,25]. Also, many researchers have used zebra-fish seizure model for anti- convulsions in zebra-fish larvae was assessed through quantification of the high-speed moved distance.…”
Section: Discussionmentioning
confidence: 99%
“…The seizure-like behavior was classified according to each stage: stage I-dramatically increased swimming activity, stage II-whirlpool swimming behavior, and stage III-clonus-like seizures, followed by loss of posture when the animal falls to one side and remains immobile for 1-3 s, as previously reported for zebrafish. 15,17 The animals were submitted to the PTZ treatment until they reached stage III. The latencies to the first episode of seizure activity in stages I, II, and III were analyzed for each animal during PTZ exposure.…”
Section: Ptz-induced Seizuresmentioning
confidence: 99%
“…13,14 Zebrafish is a small freshwater teleost that has been used as a model organism to study epilepsy. Pentylenetetrazole (PTZ)-induced seizures in zebrafish larvae 15,16 and adults 17,18 cause the behavioral and electrographic alterations that would be expected from a seizure episode. Furthermore, previous studies have demonstrated the adenosine receptor subtypes, A 1 , A 2A.1 , A 2A.2 , and A 2B , in zebrafish.…”
mentioning
confidence: 99%